Metagoverning collaborative innovation in governance networks - Sarensen, Eva; Torfing, Jacob (2017)
Western liberal governments increasingly seek to improve the performance of the public sector by spurring innovation. New Public Management reforms from the 1980s onward viewed strategic entrepreneurial leadership and public?private competition as key drivers of public innovation. By contrast, the current wave of New Public Governance reforms perceives collaboration between relevant and affected actors from the public and private sector as the primary vehicle of public innovation, and tends to see governance networks as potential arenas for collaborative innovation. The new focus on collaborative innovation in networks poses a fundamental challenge for public managers, elected politicians, and others aiming to metagovern governance networks. Hence, we claim that a specific metagovernance strategy is needed when the purpose of governance networks is to stimulate efficiency, effectiveness, and democratic legitimacy through innovation rather than incremental improvements. The article aims to sketch out the contours of such a strategy by comparing it with more traditional metagovernance strategies. The argument is illustrated by an empirical analysis of an example of collaborative innovation in Danish elderly care. - Reproduced.
Keywords: Governance network; Innovation; Governance; Public administration